Biofilmed multifarious rhizobacterial isolates of tomato rhizosphere of North-Western Himalayas promote plant growth in tomato - Kaundal, Shubham; Rana, Neerja; Kumar, Yashwant; Alhewairini, Saleh S.; Barasarathi, Jayanthi; Haron, Farah Farhanah; Rebouh, Nazih Y. (Frontiers in Plant Science, 2025)
BackgroundTomato production is often limited by poor soil health and nutrient deficits, which lower agricultural productivity. Plant growth-promoting rhizobacteria (PGPR) provide a sustainable approach to improve plant development and soil fertility.ObjectivesThe objectives of this study were to 1) isolate and screen PGPR from the rhizosphere soil of tomato-growing regions in Himachal Pradesh, India; 2) evaluate the selected PGPR for biofilm production; 3) characterize and molecularly identify the biofilm-producing isolates; and 4) assess their efficacy in enhancing tomato plant growth.MethodsForty bacterial isolates were collected from soils in Dharon Ki Dhar, Shillai, Balh, and Berthin and tested for PGPR characteristics. These included phosphate solubilization, nitrogen fixation, and the production of hydrogen cyanide, ammonia, and indole-3-acetic acid (IAA). Siderophore production and biofilm formation were also assessed. The most potent biofilm-producing isolates were identified using 16S rDNA sequencing.ResultsAmong the isolates, 28 solubilized phosphate (up to 91.2% with MB-7), 26 fixed nitrogen, 18 produced hydrogen cyanide, and 16 produced ammonia. All isolates produced IAA, with MB-7 and BB-3 producing the highest quantities (89.1 and 85.1 µg/mL, respectively). BB-3 exhibited the highest percentage of siderophore production (86.2%). BB-3 and MB-7 were potent biofilm producers. Molecular analysis identified BB-3 as Brucella rhizosphaerae and MB-7 as Delftia lacustris. Inoculation with D. lacustris greatly enhanced tomato plant growth—plant height increased by 49.14%, shoot fresh weight increased by 32.47%, and root length increased by 45.00%—as compared to uninoculated control.ConclusionD. lacustris shows significant potential as a bioinoculant for increasing tomato plant growth and can potentially be used effectively in sustainable agriculture approaches.